Le mot juste? Några tankar kring "varldens forsta produktionslexikon" - Ohlander, Sölve (LexicoNordica, 1995)
Anmeldt værk: Longman Language Activator --'- The World's First Production Dictionary 1993. Editorial Director: Della $ummers. Longman. Thls review article is focused on certain general issues arising in connection with the lexicographically innovative Longman Language Activator (1993). Since it proclaims itself "the world's first production dictionary", designed to help intermediate and advanced learners ofEnglish to go "from ideas to words", the relationship between "encoding" and "decoding" is ofparticular interest, especially with regard to different types of dictionaries. The semantic/conceptual basis of the Activator - its classification of word meanings into some thousand "Key Words" (core concepts) under which individual words and phrases are grouped - is discussed and related to other semantically sorted dictionaries, certain !imitations and problems being noted. It is argued that neither the semantic grouping nor the various types of non-semantic information provided (grammatical, sociolinguistic, collocational, etc.) are unique to the Activator. In faet, it may be regarded as an eminently useful - and on the whole userfriendly - hybrid between monolingual learners' dictionaries and synonym dictionaries or thesauruses. lts grouping of words and phrases into semantic fields should be conducive to increased coherence in vocabulary learning. Among its further strong points is the inclusion of a variety of expressions characteristic of informal spoken English.